2021
DOI: 10.3390/biom11020280
|View full text |Cite
|
Sign up to set email alerts
|

Why Does Hyperuricemia Not Necessarily Induce Gout?

Abstract: Hyperuricemia is a risk factor for gout. It has been well observed that a large proportion of individuals with hyperuricemia have never had a gout flare(s), while some patients with gout can have a normuricemia. This raises a puzzle of the real role of serum uric acid (SUA) in the occurrence of gout flares. As the molecule of uric acid has its dual effects in vivo with antioxidant properties as well as being an inflammatory promoter, it has been placed in a delicate position in balancing metabolisms. Gout seem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 109 publications
1
32
1
Order By: Relevance
“…The cause of gout is complex. Numerous studies ( Dalbeth et al, 2016 ; So and Martinon, 2017 ; Dalbeth et al, 2019 ; Clebak et al, 2020 ; Dehlin et al, 2020 ; Zhang, 2021 ) have highlighted that the environment, diet, genetics, immunity, and other aspects participate in the development of the disease in varying degrees, and gout is more prevalent in the male population. We detected the expression levels of hsa_circRNA_100632, hsa_circRNA_405646, hsa_circRNA_103,657, and hsa_circRNA_000,241 in 150 male subjects (45 AG, 45 IG, and 60 HC) using qRT-PCR and confirmed that hsa_circRNA_103657 and hsa_circRNA_000241 were significantly upregulated in the PBMCs of gout patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cause of gout is complex. Numerous studies ( Dalbeth et al, 2016 ; So and Martinon, 2017 ; Dalbeth et al, 2019 ; Clebak et al, 2020 ; Dehlin et al, 2020 ; Zhang, 2021 ) have highlighted that the environment, diet, genetics, immunity, and other aspects participate in the development of the disease in varying degrees, and gout is more prevalent in the male population. We detected the expression levels of hsa_circRNA_100632, hsa_circRNA_405646, hsa_circRNA_103,657, and hsa_circRNA_000,241 in 150 male subjects (45 AG, 45 IG, and 60 HC) using qRT-PCR and confirmed that hsa_circRNA_103657 and hsa_circRNA_000241 were significantly upregulated in the PBMCs of gout patients.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological investigations have shown that gout is closely related to hyperuricemia, hyperlipidemia, and hyperglycemia ( Dalbeth et al, 2019 ). Moreover, elevated sUA levels are considered an important risk factor for gout, and hyperuricemia is one of the independent risk factors for metabolic diseases such as hypertension, diabetes, and coronary heart disease ( Dalbeth et al, 2016 ; Zhang, 2021 ). Based on these findings, we analyzed the correlations between sUA, lipid, and glucose metabolism and the expression level of circRNAs and revealed that the expression level of hsa_circRNA_000241 was positively correlated with TG, and the expression of hsa_circRNA_103657 was positively correlated with TG and GLU and negatively correlated with HDL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such modifications are considered as important responses to environmental triggers, enabling adaptive changes of gene expression patterns (6). In the context of gout pathogenesis, epigenetic mechanisms might be of particular interest to account for the remarkable variability seen in patients (7) in terms of crisis intensity or frequency and to assess the relationship [or sometimes the absence of relationship (8)] between uricemia levels and MSU crystals-dependent joint inflammation. In line with these assumptions, it is noteworthy to highlight that genome-wide association studies (GWAS) comparing gout patients to control groups have identified variants in genes encoding important players in epigenetic regulation mechanisms, such as DNA Methyl Transferase 1 (DNMT1) (9) and lncRNAs (10).…”
Section: Introductionmentioning
confidence: 99%
“…It has been defined as SUA>7.0 mg/dL (420 mmol/l) in men; >6.0 mg/dL (360 mmol/l) in women; and >5.5 mg/dL (330 mmol/l) in children and adolescents ( 13 ). Uric acid (UA) is the final catabolic product of human exogenous and endogenous purine nucleotide metabolism ( 14 ). In most mammals, UA produced by metabolism can be degraded by uricase into 5-hydroxyisoourate and allantoin to be eliminated from the body ( 15 ).…”
Section: Manuscript Formattingmentioning
confidence: 99%